Bangus The Unabated Destiny Due to Lack of Political Leadership “Explored the Unexplored" - Showkat Ahmad Dar (Peerian Journals Publishing, 2021)
The Kashmir Valley is usually viewed as the Earth's heaven. Tourists from each locale of the globe are drawn. The tourism industry, which is famous worldwide for its natural magnificence, is one of the major financial areas of Jammu and Kashmir's state. This stunning BangusValley has monstrous potential for eco-tourists to turn into a worldwide tourist location and become the most extensive golf course in Asia. It has extraordinary potential for the tourism industry in both summer and winter. Notwithstanding, the misfortune is that it is a generally obscure station and has not been completely worked as a tourist station yet. Notwithstanding, the work is in progress on a most optimized plan of attack premise to add it to the Kashmir tourism map. There is sufficient regular vegetation, trees, and woods. It was proposed to be set up by INTACH as a Himalayan Biosphere valley. It's a quiet, serene, and mesmerizing valley. Each corner of the Kashmir Valley is said to be a tourist destination in itself. That is not an overstatement. In 2008, Bangus valley was officially declared a tourist spot. The paper aims to study the potential of Bangus valley as Eco-Tourism Spot.
Keywords: Bangus location; Minerals; Road; Covid 19